Curvas de crescimento na cultura de mucuna-anã - Candaten, Jefferson Antonio (2023)
The dwarf velvet bean is a plant of the Fabaceae family that can be used in crop rotation and intercropping systems, in nutrient cycling and biological nitrogen fixation, studies also point to other potentialities in the area of preservation and recovery of degraded areas. For research with the crop to advance, it is necessary to evaluate the behavior of growth and development and the definition of experimental protocols for the evaluation of the crop. The objective of this work was to characterize the growth of velvet bean, using non-linear models. For this, two uniformity tests were carried out at different sowing times. In each trial, weekly collections of six plants were carried out, these were weighed to obtain fresh mass data. Next, the accumulated thermal sum was calculated and the fresh mass was modeled as a function of the thermal sum using the non-linear models of Gompertz and Logistic. The two models showed good quality indicators, however, the superior performance was verified in the logistic model, which can be used to characterize the growth curves of the dwarf velvet bean. The second sowing date presented higher values of the estimates of the parameters “a”, “b” and “c” of the Logistic and Gompertz models, being the period of greater growth of the culture.